Determinants of Regional Financial Performance and Poverty Level In North Central Timor Regency - Frederic Winston Nalle; Margareta Diana Pangastuti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
This research aims to assess the financial performance of a region using the indicators of financial independence, financial dependence, and fiscal decentralization, and analyze their impact on the poverty rate in North Central Timor Regency. Time series data from 2001 to 2020 were utilized for the analysis, employing descriptive analysis and multiple linear regression. The findings indicate that the financial performance of the region remains low, signaling a reliance on external sources of income. Financial independence, financial dependence, and fiscal decentralization, both individually and collectively, exhibit a significant negative influence on the poverty rate in the area. This research underscores the importance of improving regional financial performance as a primary strategy to address poverty in North Central Timor Regency. Collaboration between the regional government and the central government is encouraged to enhance financial independence, reduce dependence, and ultimately, improve the well-being of the local population.